1997
DOI: 10.1046/j.1469-8137.1997.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the thistle gall fly, Urophora cardui, in relation to host plant nitrogen and mycorrhizal colonization

Abstract: SUMM.'VRYMany hypotheses have been developed to explain the adaptive nature of insect galls. One of these, the nutrition hypothesis, states that gall formers have advantages over other insects because gall tissue provides a better (higher quality) food source than unmodified tissue. However, this has rarely been experimentally tested. In a test of this hypothesis, we grew plants of Cirsium arvense (L.) Scop, tn a factorial design with two main treatments: the addition of nitrogen (to enhance foliar N levels) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 35 publications
2
57
1
Order By: Relevance
“…Some leaf-quality variables which are important for herbivores and which are influenced by AMF are summarised in Table 1. Several studies have shown that the growth of herbivores on mycorrhizal and non-mycorrhizal plants differs; some herbivore species performed better on mycorrhizal plants (Gange and West 1994;Gehring and Whitham 1994) while others performed better on nonmycorrhizal plants (Rabin and Pacovsky 1985;Gange and West 1994;Gehring and Whitham 1994;Gange and Nice 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Some leaf-quality variables which are important for herbivores and which are influenced by AMF are summarised in Table 1. Several studies have shown that the growth of herbivores on mycorrhizal and non-mycorrhizal plants differs; some herbivore species performed better on mycorrhizal plants (Gange and West 1994;Gehring and Whitham 1994) while others performed better on nonmycorrhizal plants (Rabin and Pacovsky 1985;Gange and West 1994;Gehring and Whitham 1994;Gange and Nice 1997).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Gange and West (1994) found that reducing mycorrhizal levels of ®eld-grown Plantago lanceolata L. resulted in higher levels of damage by chewing insects, while a laboratory trial demonstrated that performance of the generalist chewing insect Arctia caja L. was lower on highly mycorrhizal plants. Meanwhile, Gange and Nice (1997) demonstrated that the performance of the thistle gall¯y, Urophora cardui (L.) Scop., was increased if natural levels of mycorrhizal colonization of its host plant were reduced by fungicide application. Root-feeding insects may also be negatively aected by AM fungi, as found that survival and growth of black vine weevil, Otiorhynchus sulcatus (Fab.…”
Section: Introductionmentioning
confidence: 99%
“…However, additional studies with two of these species-Plantago lanceolata (Gange and West 1994) and soybean (Rabin and Pacovsky 1985)-demonstrated a decline in herbivore fitness on host plants associated with mycorrhizal fungi, suggesting a need for further study. Studies found that in five out of nine perennial species examined-cottonwood (Gehring and Whitham 2002), Scots pine (Manninen et al 1998(Manninen et al , 1999(Manninen et al , 2000, Cirsium arvense (Gange and Nice 1997), oak (Rieske 2001), and perennial rye grass (Vicari et al 2002)-herbivore fitness declined on host plants associated with mycorrhizal fungi. However, in two out of five of these species-cottonwood (Gehring and Whitham 2002) and Scots pine (Manninen et al , 2000-different herbivores also saw an increase in fitness when feeding on mycorrhizal hosts.…”
Section: Plant Successional Statusmentioning
confidence: 99%